The barriers against childhood immunizations: a qualitative research among socio-economically disadvantaged mothers - TOPUZOĞLU, AHMET; AY, NADİYE PINAR; HIDIROĞLU, SEYHAN (OXFORD UNIV PRESS, 2007)
Background: The socio-economically disadvantaged populations are among the most vulnerable groups that are under-vaccinated. Therefore, the aim of this qualitative study was to understand the behaviours of mothers concerning the immunization of their children, the decision-making process, the perceived barriers, and the enabling factors to access the services in a suburban population in Istanbul. Method: Eight focus group discussions and two in-depth interviews were carried out with the mothers who have children younger than five years. Results: While the responsibility of immunization was left totally to the mother, the socially subordinate role of women did not provide the means of getting the immunization services. The women were dependent mostly on social networks for getting the immunization services. Another important barrier to the services was related to the economical constraints and accessibility of the services. In addition, the lack of effective communication and information transfer between the health personnel and the mothers formed an important obstacle. Conclusion: This study underlines a need for an effective counselling tailored to the immunization session, which will maintain a positive relationship between the personnel and the mother.
Keywords: barriers; immunization; qualitative; Turkey; vaccination; EASTERN TURKEY; SOCIODEMOGRAPHIC FACTORS; CHILDREN; VACCINATION; SEROPREVALENCE; PERCEPTIONS; DISEASES; PARENTS; POLICY